Low field operation of hot electron light emitting devices: quasi-flat-band model - Wah, J.Y.; Balkan, N. (2004)
Several novel laterally biased HELLISH (hot electron light emission and lasing in semiconductor heterostructure) devices have previously been reported and demonstrated. These light emitting devices are normally operated at high applied fields to heat carriers to a point where they can transfer into the quantum well via tunnelling or thermionic emission. However, it has been observed that, in most devices, light emission occurs at relatively low applied fields. In this region, the fields are too low for significant heating of carriers. Therefore, the mechanism for light emission in this region cannot be explained by hot electron effects. The results illustrating the low field operation of HELLISH devices are presented together with a quasi-flat-band model.